A Study on the Ecology and Trends In the Brahmaputra Valley During the Ancient Period: Exploring the agricultural and religious dynamics in the Brahmaputra Valley during ancient times (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The agricultural landscape in the Brahmaputra valleywitnessed a change with the onset of land grants made from the 5thto the 13th centuries. The agricultural production may have beenclosely tied to the temples. Ludden opines that a transactional nexus laybehind these land grants involving Brahmans who were Vedic scholars, ritualistsand temple administrators with the agricultural communities who were farmers,herders, artisans, and merchants. The Brahmans emerge as the mainbeneficiaries. The earlier inscriptions upto the 9th century recordgrants being made to temples either in the form of a bell or a cave.